MANAJEMEN KEPALA SEKOLAH DALAM MEMBANGUN HUBUNGAN SUMBER DAYA MANUSIA DALAM PENDIDIKAN ISLAM - Robiatul Andawiyah,; Hamdani,; Maimun, (re-JIEM (Research Journal of Islamic Education Management), 2024)
In Islamic education, building relationships between human resources is the most important thing to create a harmonious climate and efforts to achieve institutional goals. The aim is to explore the management efforts made by school principals in building human resource relationships. The method used is a library research method. The primary data is a study of school principal management and building HR relationships, while secondary data is obtained from supporting literature related to the context of this research. Then, the analysis process goes through the stages of sorting and selecting (reduction), presenting it (presentation), and drawing conclusions (conclusions). This research found that school principals in building relationships between human resources were studied in two ways, including: 1) The process of building relationships between teachers can be done by emphasizing communication between teachers through coordination in every educational activity. 2) Building relationships between teachers and students can be done through a management process which includes planning, organizing, mobilizing and controlling, which is included in every institutional activity, such as in activities with a socio-emotional approach or a religious approach.